Analisis Kualitas Produksi Pupuk Organik Berbahan Dasar Limbah Media Budidaya Lalat Tentara Hitam (Hermetia illucensi) - Yogi Nirwanto; Nurul Risti Mutiarasari (Paspalum: Jurnal Ilmiah Pertanian, 2022)
Utilization of organic waste from the rest of the black soldier fly (BSF),cultivation media into organic fertilizer that meets quality standards and is efficient in its manufacture. Theidentification of the effect of various types of organic waste making up the cultivation media on the growth of BSFlarvae, the quality of organic fertilizers, the level of efficiency in the production of organic fertilizers based on therest of the cultivation media. The research implementation method is an experimental field experiment to identifythe effect of various types of waste/organic materials that make up the cultivation media on the growth of BSFlarvae to produce organic fertilizer. The results of the analysis showed that the temperature of the larval growthmedia as a result of the study ranged from 26.2 - 30.5˚C which is still included in the category that is quite idealbecause the larvae can grow and develop. The average value of the optimum pH ranged from 6.5 to 7.5, indicatingthewiderangeoftoleranceforalltypesoforganicwasteintheformer larvalmedia.Thegrowthoflarvaeonday5inthetreatmentoflayinghenswassignificantlydifferentcomparedtoothermedia,havingthelowestvalueof 0.60 g, while the final weight of larvae in treatment C and D had an average value of 0.10. Based on this,treatments C and D have the highest average value. Organic fertilizer test results from the former laying henswaste media produced a quality close to the Ministry of Agriculture's organic fertilizer quality standard, withparameters pH:H2O, C-Organic,P2O5HCL25%andK2OHCL 25%.